Tupistra annamensis (Asparagaceae), a new species from central Vietnam - Lý, Ngọc-Sâm; Hoàng, Thanh Sơn; Nguyen, Khang Sinh; Тanaka Noriyuki (Phytotaxa, 2022)
Tupistra annamensis, a new species from central Vietnam is described and illustrated. In the habitats it occurs as an epiphyte or a lithophyte. Having a pendulous scape, this species is similar to such species as T. fungilliformis and T. clarkei, but differs distinctly from them and all other members of this genus by its outer and inner floral bracts subsimilar in size and shape, and sharply acute or aristate, somewhat glumaceous bracts exceeding the flowers. Besides data on the morphological and ecological traits of the new species, we provide notes on its systematic relationships as well.